Exploring the challenges and the implementation of lean practices under lean transformation project in Malaysian small and medium enterprises - Azyyati Anuar,; Norasmah Othman,; Daing Maruak Sadek,; Norsiah Hami,; Nur Syazwanie Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to explore the challenges and the implementation of lean practices by Small and Medium Enterprises (SMEs) in Malaysia. It was conducted as a multiple-case study based on six companies that participated in the Lean Transformation Project (LTP) organized by the Malaysia Productivity Corporation (MPC). Data were collected through a combination of observation, document analysis, and semi-structured interviews. The findings revealed significant improvements in the companies after participating in the LTP. These improvements included enhancing material handling processes through proper labeling and arrangement of materials. This study provides valuable insights for academics and practitioners on the impact of lean practices on operational activities in SMEs, particularly in the Malaysian context. It highlights the significance of lean principles in driving positive changes in companies, focusing on improving process outputs and outcomes.